Peranan Taman Bacaan Masyarakat Sebagai Sumber Belajar Rumah Singgah Anak Mandiri Yogyakarta - Rohmaniyah Rohmaniyah; Marwiyah Marwiyah (Perpustakaan Nasional, 2020)
This research studies the role of TBM as a source of learning, an effort made by TBM to make children interested in learning at TBM, namely by providing learning that makes the horizon of knowledge more broad and developing. Data collection techniques used are through interviews, observation and documentation. The role of TBM as a learning resource by supporting the pursuit of learning packages that are currently being carried out by children in preparation for the exam. In supporting children to get chase packages, foundation management must provide supporting books available at TBM. Activities undertaken by TBM in order to be close to street children are by making direct visits to the location of street children who usually gather and do storytelling activities so that children who cannot read can be helped and understand the meaning of the story. Constraints that have occurred namely regarding the compilation of children who are difficult to read because of differences in nature.